Educational Needs on Infant Feeding Among Mothers Attending an Urban Integrated Health Centre in Ebolowa, Cameroon: A Cross-Sectional Study - EBEH, Claude Eugène; MBOM, Raquel Perdy; MBITA, Axel Mintya; METSAGUE, Kelly; TANGA, Miguelle Nogning; FOBASSO , Bolivar Dékou; MANG, Yannick Dimitry (African Journal of Nutrition and Dietetics, 2026)
Infant feeding is critical for child growth and health, particularly during the transition from exclusive breastfeeding to complementary feeding. Inadequate maternal knowledge and suboptimal feeding practices, as defined by predefined criteria, may compromise infant health, while vaccination services offer a strategic opportunity for nutrition education. A descriptive cross-sectional study was conducted from May 26 to August 26, 2025, at CSI Urban No.2 in Ebolowa, Cameroon, among 120 mothers of children aged 0-24 months. Data were collected using structured questionnaires. Chi-square and ANOVA tests were performed, with statistical significance set at p < 0.05. The mean maternal age was 25.42 ± 6.07 years. Although 83.33% of mothers reported exclusive breastfeeding for 6 months, only 41.67% met the criteria for appropriate exclusive breastfeeding practice, indicating a gap between reported knowledge and actual practice. Among mothers reporting six months of exclusive breastfeeding, 50.83% had low knowledge scores and 32.5% had moderate scores. A statistically significant association was observed between reported exclusive breastfeeding duration and overall nutritional knowledge scores (p = 0.0001). Complementary feeding was introduced at six months by 65% of mothers, at nine months by 31.67%, and at four months by 2.5%. Knowledge of complementary feeding was low in 58.33% and moderate in 41.67%, with no significant association with the timing of introduction (p > 0.05). Foods considered appropriate for children aged 6-12 months included milk and dairy products with fruits and vegetables (43.33%), meat, fish, and eggs (30%), and cereals and tubers (26.67%). Sugar avoidance was correctly reported by 59.17% of mothers. Overall, maternal knowledge and infant feeding practices were predominantly suboptimal, underscoring the need for strengthened, behavior-focused nutrition education integrated into routine vaccination services.